Regulation of Satiety Quiescence by Neuropeptide Signaling in Caenorhabditis elegans - Makino, Mei; Ulzii, Enkhjin; Shirasaki, Riku; Kim, Jeongho; You, Young-Jai (Frontiers in Neuroscience, 2021)
Sleep and metabolism are interconnected homeostatic states; the sleep cycle can be entrained by the feeding cycle, and perturbation of the sleep often results in dysregulation in metabolism. However, the neuro-molecular mechanism by which metabolism regulates sleep is not fully understood. We investigated how metabolism and feeding regulate sleep using satiety quiescence behavior as a readout in C. elegans, which shares certain key aspects of postprandial sleep in mammals. From an RNA interference-based screen of two neuropeptide families, RF-amide (FLPs) and insulin like peptides (INSs), we identified flp-11, known to regulate other types of sleep-like behaviors in C. elegans, as a gene that plays the most significant role in satiety quiescence. A mutation in flp-11 significantly reduces quiescence, whereas over-expression of the gene enhances it. A genetic analysis shows that FLP-11 acts upstream of the cGMP signaling but downstream of the TGFβ pathway, suggesting that TGFβ released from a pair of head sensory neurons (ASI) activates FLP-11 in an interneuron (RIS). Then, cGMP signaling acting in downstream of RIS neurons induces satiety quiescence. Among 28 the INSs genes screened, two INS genes, ins-1 and ins-7, known to play a significant role in starvation-associated behavior working in AIA and URX, respectively, are inhibitory to satiety quiescence. Our study suggests that specific combinations of neuropeptides are released, and their signals are integrated in order for an animal to gauge its metabolic state and to control satiety quiescence, a feeding-induced sleep-like state in C. elegans.